Using Cooperative Learning Strategy to Improve Writing Skills of Grade Ten Students of Senior High School - Qoriatus Saidah Marhamah; Erniwati; Syahrul Munir; Sriati Usman (Universitas Islam Negeri Palopo, 2025)
The objective of this research is to find out if using Cooperative Learning Strategy can improve students’ writing skills of grade ten students at Senior High School. The researcher applied quasi-experimental design with two classes, experimental class and control class. The experimental class consisted of 34 students and control class consisted of 35 students selected through cluster random sampling technique. In collecting data, the researcher administered pretest and posttest to both the experimental class and control class. The data were analyzed statistically in order to find out the significant difference of students’ achievement before and after treatments. Using 0.025 level of significance and 67 degrees of freedom (df), the researcher found that the value of t-table was 1.998, which was lower than the t-counted 3.57. It means that the hypothesis is accepted. In other words, using Cooperative Learning Strategy can improve students’ writing skills.